2002
DOI: 10.1128/aem.68.12.6439-6445.2002
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Properties and Serotypes of Shiga Toxin-Producing Escherichia coli from Healthy Australian Cattle

Abstract: The virulence properties and serotypes of complex Shiga toxin-producing Escherichia coli (cSTEC) were determined in two studies of healthy cattle in eastern Australia. In the first, a snapshot study, 84 cSTEC isolates were recovered from 37 of 1,692 (2.2%) fecal samples collected from slaughter-age cattle from 72 commercial properties. The second, a longitudinal study of three feedlots and five pasture beef properties, resulted in the recovery of 118 cSTEC isolates from 104 animals. Of the 70 serotypes identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
55
1
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 35 publications
(23 reference statements)
9
55
1
3
Order By: Relevance
“…Only Lira et al (2004) have reported the isolation of STEC strains from mastitic milk, the carriage of stx gene (12.08%) and the distribution of 22.7% (stx 1) and 45.5% (stx 2) genes. This agrees with the results reported in the present study: stx carriage (8.6 %), was distributed between 40.0% (stx 1), and 60.0% (stx 2), with a predominance of stx 2 gene in both studies, in agreement with the results of Hornitzky et al (2002) in Australia, Zschok et al (2000), in Germany, and Irino et al (2005), in Brazil.…”
Section: Discussionsupporting
confidence: 83%
“…Only Lira et al (2004) have reported the isolation of STEC strains from mastitic milk, the carriage of stx gene (12.08%) and the distribution of 22.7% (stx 1) and 45.5% (stx 2) genes. This agrees with the results reported in the present study: stx carriage (8.6 %), was distributed between 40.0% (stx 1), and 60.0% (stx 2), with a predominance of stx 2 gene in both studies, in agreement with the results of Hornitzky et al (2002) in Australia, Zschok et al (2000), in Germany, and Irino et al (2005), in Brazil.…”
Section: Discussionsupporting
confidence: 83%
“…EHEC hemolysin, which causes an enterohemolytic phenotype on blood agar, was detected in many STEC strains of different origins (12,13,28,29,69) and was found to be significantly associated with eae-positive STEC strains belonging to classical and emerging EHEC types (13,28,46,69,76). Similar findings were made in our study, where EHEC hemolysin was detected in 96.2% of the eae-positive STEC strains.…”
Section: Discussionsupporting
confidence: 79%
“…By this list, we could identify 41 STEC strains belonging to 31 different serotypes which were not previously described as human STEC (Tables 1 and 2). Some of these "new" O:H types were already reported to be STEC strains from animals, and it was shown that certain STEC serotypes are closely associated with some animal host species (12,26,29,41,53,78,79). Based on these reports, we made an estimate about the possible animal source of the STEC strains from our study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations